2021
DOI: 10.3390/molecules26154652
|View full text |Cite
|
Sign up to set email alerts
|

Structure Solution of Nano-Crystalline Small Molecules Using MicroED and Solid-State NMR Dipolar-Based Experiments

Abstract: Three-dimensional electron diffraction crystallography (microED) can solve structures of sub-micrometer crystals, which are too small for single crystal X-ray crystallography. However, R factors for the microED-based structures are generally high because of dynamic scattering. That means R factor may not be reliable provided that kinetic analysis is used. Consequently, there remains ambiguity to locate hydrogens and to assign nuclei with close atomic numbers, like carbon, nitrogen, and oxygen. Herein, we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(119 reference statements)
0
5
0
Order By: Relevance
“… 36 , 38 Alternatively, selective dipolar recoupling specific to one spin pair may be employed. 115 117 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 , 38 Alternatively, selective dipolar recoupling specific to one spin pair may be employed. 115 117 …”
Section: Discussionmentioning
confidence: 99%
“…(ii) The (large) spin system was approximated by a smaller counterpart of 2–4 spins, ,,, with the internuclear distances varied to fit the NMR-signal buildup to the experimental counterpart. Such internuclear-distance extraction procedures have been applied extensively to “isolated” spin pairs, such as 13 C– 13 C pairs in organic/biological samples, ,,, where specific 13 C-site labeling in conjunction with diluting the 13 C– 13 C pairs by co-crystallization with a natural abundance material is often straightforward. , Alternatively, selective dipolar recoupling specific to one spin pair may be employed. …”
Section: Discussionmentioning
confidence: 99%
“…For L-histidine.HCl.H2O deuterated from water-d at room temperature (295 ±3 K), the H/D exchange yields are in the range of 20-36% for different labile sites such as -NH in the heterocycle, NH3 and water protons, however, a high degree of H/D exchange of up to 90% can be obtained by recrystallizing the same compound at elevated temperatures. [19] Relatively high yields of deuteration and shorter relaxation delays associated 2 H sites allow us to rapidly detect a 2 H MAS spectrum (Figure 1b), in which the water-D, ND3 and the D7/D5 peaks (10)(11)(12)(13)(14)(15)(16)(17)(18) ppm are observed.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Additionally, ssNMR in conjunction with diffraction-based techniques and modelling approaches (for example, NMR crystallography) is increasingly applied to determine the three-dimensional structures of (semi)crystalline and amorphous solids. [11][12][13][14][15][16][17] A large number of elements in the periodic table exhibit more than one NMR active isotope such as 1 H/ 2 H, 6 Li/ 7 Li, 10 B/ 11 B, 14 N/ 15 N, 35 Cl/ 37 Cl, 47 Ti/ 48 Ti and 85 Rb/ 87 Rb, to name a few. However, only a handful of studies have reported the solid-state 2D correlation NMR spectra of isotopes of the same nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Applications have been presented in the areas of optoelectronics, catalysis, biomacromolecules, pharmaceutical formulations, energy harvesting and storage materials [1][2][3][4][5][6][7]. In addition, ssNMR, in conjunction with diffraction-based techniques and modelling approaches (also referred to as NMR crystallography), is increasingly applied to characterize the intermolecular interactions and to determine the three-dimensional structures of (semi)crystalline and amorphous solids [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%